Building Employee Work Effectiveness Through Competence And Communication: A Study Of Cv Sejahtera Sukses Gemilang Medan - Candra; Clarrissa Winata; Calista (CV Edujavare Publishing, 2026)
Employee work effectiveness is a key factor in achieving organizational goals. Work effectiveness is influenced by several factors, particularly competence and communication. This study aims to examine the effect of competence and communication on employee work effectiveness at CV Sejahtera Sukses Gemilang Medan. A quantitative approach with a survey method was employed. The population consisted of 59 employees, all of whom were selected as respondents using a saturated sampling technique. Data were collected through questionnaires and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination (R²) with IBM SPSS Statistics. The results indicate that competence has a positive and significant effect on employee work effectiveness. Communication also has a positive and significant effect and is the most dominant variable influencing work effectiveness. Simultaneously, competence and communication significantly affect employee work effectiveness, with a coefficient of determination (R²) of 97.9%, indicating that most of the variation in work effectiveness is explained by these two variables. The findings highlight that improving employee competence supported by effective organizational communication is essential for enhancing work effectiveness and achieving organizational objectives